An Analysis of Students’ Lexical Choice in Writing Descriptive Text - Lucky Indra Pratama; Totok Hari Prasetiyo; Rizki Nurfida Pambayun (LUNAR, 2022)
Writing is become the one of difficult skill to learn especially in EFL context. Students have problems when formulating words while doing writing assignments. This very important to investigate student problem while do writing especially on lexical choice that student utilize in writing descriptive. The corpus can also be used for examines sentence writing structure and word selection that can be seen and synchronized very effectively. The importance of this research is to be able to know the capacity of students when doing writing task and how their writing product can be better. it can be ascertained that from student writing samples that have been analyzed, there are 10.2% high frequency, 2.5% mid frequency, and 87.3% low frequency. This identifies that in writing students still tend to use familiar words to make a sentence. Based on the aspects of discovery that have been mentioned, students' ability to write still needs to be improved again, especially in the selection of several adjectives and pronouns.